PENGARUH PENERAPAN MODEL PEMBELAJARAN PREDICT OBSERVE EXPLAIN (POE) TERHADAP AKTIVITAS BELAJAR KIMIA SISWA MAN KUOK - navisa navisa; Pangaloan soleman ritonga (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Abstract This research was an experiment—instigated by the lack of students’ activeness in the teaching learning process. This research aimed at informing that Predict Observe Explain (POE) learning model effected students’ Chemistry learning activity on Electrolyte and Non-Electrolyte Solution material at State Islamic Senior High School of Kuok. The samples were 29 students of class X.1 (Experimental group) and 31 students of class X.3 (Control group). Interview, normality test of observation sheets, and documentation were the techniques of collecting the data. T-test was used to analyze the data. Based on the data analysis, tobserved was 2.200 and ttable was 2.00 (tobserved ≥ ttable). It revealed that Ho was rejected. In other words, it showed that there was students’ Chemistry learning activity enhancement on Electrolyte and Non-Electrolyte Solution material at State Islamic Senior High School of Kuok. The influence is counted by using Influence Coefficient (IC) Predict Observe Explain (POE) learning model it is 7,7%. Keywords:Predict Observe Explain (POE)Model, Learning Activity, Electrolyte and Non-Electrolyte Solution